PERJANJIAN BELI KEMBALI (BUY BACK GUARANTEE) YANG DIBUAT ANTARA PENGEMBANG DAN BANK DALAM PENYELESAIAN MASALAH KREDIT MACET - Dominika, Retno Wahyurini; Kawuryan, Endang Sri (Lex Journal: Kajian Hukum & Keadilan, 2017)
The type of research used in this study is normative legal research, which according to Peter Mahmud Marzuki, "Legal research is a study that analyzes the factual situation and applies the legal doctrines that have been formed. Relying on the theory of justice and the protection of the law, the principle of the law of guarantee does not abandon the principle of principle in the Agreement theory and the implementation of the prudential principle in the banking world which underlies the emergence of buy back guarantee. This study further considers developer interest and practice in the field the notary to analyze the form of legal relationship and accountability between Debtor, Bank, and Developer which is subject to the buyback guarantee to be able to provide legal protection for the developer in case of retrieving object Guarantee. Finally in this study the authors conclude that the relationship between the Bank with the debtor/buyer who made the purchase of housing units with credit facilities Home Ownership of the Bank is regulated in a credit agreement with a guarantee with accountability Banks provide mortgage facilities and borrowers are obliged to pay installments, while the legal relationship between banks With the developer arranged in a buy back guarantee agreement, whereby the bank and the developer have entered into and signed a cooperation agreement stipulating that the developer is fully responsible and binding itself as a guarantor for the payment of the entire amount owed by the debtor/ buyer to the bank if the debtor/ buyer has Neglect obligations to the bank, then between the developer and the debtor / buyer the legal relationship arising is through the subrogation institution, where the payment of the debtor / purchaser's debt by the developer to the bank raises the subrogation or the change of the debtor's rights (A bank) by a third (developer) who pays the debtor (the bank) therefore as a form of legal protection for the developer to retrieve the collateral object if the developer executes the contents of the buy back guarantee, is the Subrogation Deed.